Complexes: Role in Pharmaceutical Formulation - BHALEKAR, M.; MADGULKAR, A.; PATEL, BHAVIN; SHRIKHANDE, V. (Asian Journal of Chemistry, 2010)
Complexation is a frequent form of interaction between drugs and excipients. Complexation has beneficial as well as deleterious effects. This is a review of research findings reporting complexation as a tool to overcome problems such as stability, safety, bioavailability and dissolution. The information on important complex types, material and applications is included in this review.